2007
DOI: 10.1016/j.seppur.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic oxidation of ammonia from MAP decomposition

Abstract: The Cu/TiO 2 catalysts with different Cu loadings were prepared, and their performance in the selective catalytic oxidation of ammonia (SCO of NH 3 ) was compared with 10% Cu/Al 2 O 3 . The 10% Cu/TiO 2 has the best performance among its series for NH 3 conversion and N 2 selectivity. At 250• C, the 100% conversion of ammonia was achieved and the selectivity to N 2 came to 95%. The 10% Cu/TiO 2 catalyst has a much higher activity for the SCO of ammonia and a slightly lower N 2 selectivity than 10% Cu/Al 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 21 publications
(29 reference statements)
2
22
0
Order By: Relevance
“…4b). Comparing the obtained results with that reported in the scientific literature it could be concluded the studied catalyst is significantly less sensitive to the presence of water vapour than other active Cu-doped catalysts of the SCO process (e.g., Cu/TiO 2 [8], Cu/Al 2 O 3 , CuY [9,10]). …”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…4b). Comparing the obtained results with that reported in the scientific literature it could be concluded the studied catalyst is significantly less sensitive to the presence of water vapour than other active Cu-doped catalysts of the SCO process (e.g., Cu/TiO 2 [8], Cu/Al 2 O 3 , CuY [9,10]). …”
Section: Resultssupporting
confidence: 64%
“…Copper oxide deposited on alumina, titania, and zeolites exchanged with copper were found to be active and selective catalysts for the low-temperature SCO process, however, their catalytic performance was significantly decreased by the presence of water vapour in the reaction mixture [7][8][9][10]. Hung [11] has shown high activity of a CuO/La 2 O 3 oxide system obtained by the co-precipitation method, while Cui et al [6] reported high activity and selectivity to nitrogen of the mesoporous CuO/RuO 2 catalysts obtained by a co-nano casting-replication method.…”
Section: Introductionmentioning
confidence: 99%
“…The bands at 1614 and 1232 cm À1 could be assigned to the asymmetric and symmetric deformation modes of NH 3 coordinated on Lewis acid sites [6,[20][21][22][23], respectively. Correspondingly, the bands in the NH stretching region were also observed at 3401, 3356, 3270, and 3149 cm À1 [8,14,25].…”
Section: Ftir Study Of Nh 3 Adsorptionmentioning
confidence: 82%
“…The bands at 1581 and 1377 cm À1 were assigned to amide (-NH 2 ) scissorings and (-NH 2 ) waggings, respectively. The band at 1456 cm À1 was ascribed to -NH deformation modes [8,14,24,25]. These results indicate that upon heating, the adsorbed NH 3 can be activated to form -NH 2 and -NH intermediates through abstraction of hydrogen.…”
Section: Ftir Study Of Nh 3 Adsorptionmentioning
confidence: 82%
“…He et al [7,16,17] have shown that smaller CuO particle is deposited on Al 2 O 3 than TiO 2 and the N 2 selectivity is related with CuO particle size. Sultana et al [17] have also concluded that the ratio of MnO 2 /MnO 3 formation in Mn supported catalysts strongly depends on the nature of the support.…”
Section: Introductionmentioning
confidence: 99%